2020
DOI: 10.1038/s41467-020-19137-6
|View full text |Cite
|
Sign up to set email alerts
|

Pattern recognition based on machine learning identifies oil adulteration and edible oil mixtures

Abstract: Previous studies have shown that each edible oil type has its own characteristic fatty acid profile; however, no method has yet been described allowing the identification of oil types simply based on this characteristic. Moreover, the fatty acid profile of a specific oil type can be mimicked by a mixture of 2 or more oil types. This has led to fraudulent oil adulteration and intentional mislabeling of edible oils threatening food safety and endangering public health. Here, we present a machine learning method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…These studies have demonstrated the substantial potential for applying LF-NMR relaxometry for the rapid identification of oil adulteration. However, subsequent research has demonstrated that the identification capability of conventional LF-NMR relaxometry is often limited by the fact that the relaxation properties of individual edible oils can be very similar to those of complex mixtures including two or more edible oils [ 27 ]. As a result, the relaxation properties of edible oils captured by conventional LF-NMR spectroscopy may lack the discrimination capability required for meeting the needs of public safety and business interests.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have demonstrated the substantial potential for applying LF-NMR relaxometry for the rapid identification of oil adulteration. However, subsequent research has demonstrated that the identification capability of conventional LF-NMR relaxometry is often limited by the fact that the relaxation properties of individual edible oils can be very similar to those of complex mixtures including two or more edible oils [ 27 ]. As a result, the relaxation properties of edible oils captured by conventional LF-NMR spectroscopy may lack the discrimination capability required for meeting the needs of public safety and business interests.…”
Section: Introductionmentioning
confidence: 99%
“…As the composition of crude oil is highly variable, depending upon the plant species, geographical location of the source and method of oil extraction [28]. Additionally, unintentional or intentional use of cheaper (i.e., lower quality), less pure, or mislabeled raw materials can occur during the oil blending or extraction process [29,30]. Addition of unwanted additives or mislabeling (especially if a manufacturer produce several type of oil blends in parallel) could also occur within the final product [29,30].…”
Section: Selection Of Marker Fatty Acids Per Oil Blendmentioning
confidence: 99%
“…Additionally, unintentional or intentional use of cheaper (i.e., lower quality), less pure, or mislabeled raw materials can occur during the oil blending or extraction process [29,30]. Addition of unwanted additives or mislabeling (especially if a manufacturer produce several type of oil blends in parallel) could also occur within the final product [29,30]. This might also explain why some trace fatty acids (i.e, < 1 g/100 g) are lost when the standard mixture profile (n = 22 fatty acids) is compared with those profiles obtained in commercial samples (n = 7 fatty acids).…”
Section: Selection Of Marker Fatty Acids Per Oil Blendmentioning
confidence: 99%
“…Therefore, it is of paramount importance to continuously monitor the quality of food. Rapid screening of food and beverages, including edible oils, has become a key focus among scientists and industrialists because contamination and adulteration of food compromise the quality of food [1]- [3]. In this context, the need for accurate, fast, non-destructive, and economical methods to assure the standard of food are of a timely need.…”
Section: Introductionmentioning
confidence: 99%